Analisis Spasial Deforestasi Kawasan Hutan Lindung di Kecamatan Sangir Kabupaten Solok Selatan - Algif Fahri; Hendry Frananda (Jurnal Zona, 2025)
Protected forests play a crucial role in maintaining ecological balance, safeguarding biodiversity, and reducing disaster risks. However, human activities such as agricultural expansion, infrastructure development, and land conversion have triggered significant deforestation. Spatial monitoring of land cover change is essential to understand degradation patterns as a basis for conservation policies. This study aims to analyze land cover changes in the protected forest of Sangir Subdistrict from 2018 to 2025 and to identify spatial patterns of deforestation. The research employed Sentinel-2 imagery classified using the Random Forest algorithm into five classes: forest, cropland, open land, plantation, and rice field. Validation results showed overall accuracies of 0.84 (2018) and 0.82 (2025). The findings reveal that forest area decreased by 449.69 ha (−9.95%), mainly in forest–cultivation transition zones and areas near roads and rivers. Spatially based conservation policies are urgently needed to mitigate deforestation